Anthocyanins content of methanol extract of parijoto (Medinilla speciosa) and its effect on serum malondialdehyde (MDA) level of hyperlipidemic rat - NOOR NAILIS SA’ADAH; ADEK MAYANG INDIANI; AWIK PUJI DYAH NURHAYATI; NOVA MAULIDINA ASHURI (Smujo International, 2019)
Abstract. Sa’adah NN, Indiani AM, Nurhayati APD, Ashuri NM. 2019. Anthocyanins content of methanol extract of parijoto (Medinilla speciosa) and its effect on serum malondialdehyde (MDA) level of hyperlipidemic rat. Nusantara Bioscience 11: 112-118. Parijoto (Medinilla speciosa) is an endemic plant in Indonesia that its fruit have a purplish red color, which indicated that parijoto fruits contain anthocyanins, pigments of the flavonoid class that responsible for the red, blue and purple coloration of many flowers and fruits. This study was aimed to determine the total yield of extract and anthocyanins content of methanol extract of parijoto (Medinilla speciosa) pericarp and whole fruit and the effect of parijoto whole fruit extract on serum malondialdehyde (MDA) level of the hyperlipidemic rats. Extraction of parijoto fruit and pericarp were carried out by the maceration method with methanol as a solvent. Determination of the total anthocyanin was done by pH difference method. MDA serum levels were done in a pre-test and post-test Randomized controlled group design was used in this study. Rats were divided into five groups: normal rats, hyperlipidemic rats, hyperlipidemic rats treated with methanol extract of parijoto (500 mg · kg ?1, 1000 mg · kg ?1, and 1500 mg · kg?1 body weight). Blood was collected at hyperlipidemia state and after treatment of methanol extract of parijoto for determination of MDA level in blood serum. The results showed that the total yield of parijoto pericarp extract and the whole fruits were 11.46 g (3.18% ) and 9.02 g (2.88%) respectively. Anthocyanins content of parijoto pericarp and whole fruit extracts  were 208.75 mg · L-1 and 173.7 mg · L-1. Administration of methanol extract of whole fruit parijoto  in hyperlipidemic rats reduced serum MDA levels significantly (p < 0.01), from 14.88 nmol · mL-1 to 8.63 nmol · mL-1.